System Analysis and Artificial Intelligence - Zgurovsky, Michael; Pankratova, Nataliya (Studies in Computational Intelligence, 2023)
This book contains the latest scientific work of Ukrainian scientists and their colleagues from other countries of the world in three interrelated areas: systems analysis, artificial intelligence and data mining. The included articles present the theoretical foundations and practical applications of the latest tools and methods of artificial intelligence, scenario planning, decision making and computational intelligence for important areas of human activity. The tools and methods presented in the book are continuously evolving and finding new applications across various fields, contributing to advancements and efficiencies in different industries: healthcare, finance, retail and E-commerce, manufacturing and industrial automation, transportation and logistics advancements and cybersecurity. The results of the book are useful to teachers, scientists, graduate students of universities and managers of large companies specializing in strategic planning, engineering design of complex systems, decision-making, optimization of operations and other related fields of knowledge and practice